2021
DOI: 10.3390/antiox10111764
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Superoxide Dismutase Concentrations in Obstructive Sleep Apnoea (OSA): A Systematic Review and Meta-Analysis

Abstract: Obstructive Sleep Apnoea (OSA) is characterized by a pro-oxidant state that results from the recurrent hypoxia-reoxygenation cycles. Superoxide dismutase (SOD), a key antioxidant enzyme involved in the detoxification of superoxide radicals, could represent a reliable marker to monitor the antioxidant defences in OSA. In order to capture and critically appraise the available evidence, we performed a systematic review and meta-analysis of studies reporting SOD concentrations in OSA patients and non-OSA controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Malondialdehyde (MDA) is the typical product of lipid peroxidation, in which process free radicals attack lipids containing carbon-carbon double bond(s), such as polyunsaturated fatty acids [ 9 ]. The body antioxidant defenses contain the enzymatic scavenger of RONS by superoxide dismutase (SOD), which can convert superoxide (O 2 •− ) into oxygen and hydrogen peroxide [ 10 ]. Total antioxidant capacity (TAC), also named nonenzymatic antioxidant capacity, is usually evaluated as the moles of oxidants neutralized by one liter of body fluids [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malondialdehyde (MDA) is the typical product of lipid peroxidation, in which process free radicals attack lipids containing carbon-carbon double bond(s), such as polyunsaturated fatty acids [ 9 ]. The body antioxidant defenses contain the enzymatic scavenger of RONS by superoxide dismutase (SOD), which can convert superoxide (O 2 •− ) into oxygen and hydrogen peroxide [ 10 ]. Total antioxidant capacity (TAC), also named nonenzymatic antioxidant capacity, is usually evaluated as the moles of oxidants neutralized by one liter of body fluids [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…•− ) into oxygen and hydrogen peroxide [10]. Total antioxidant capacity (TAC), also named nonenzymatic antioxidant capacity, is usually evaluated as the moles of oxidants neutralized by one liter of body fluids [11].…”
Section: Introductionmentioning
confidence: 99%
“…However, the high co-occurrence rate suggests a possible partly pathophysiological overlap between depressive and sleep apnoea syndromes. The chronic low-grade inflammation (CLGI), oxidative stress, or microbiota dysfunction are all interplaying biological mechanisms that have been suggested [1,5,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A pro-oxidant state in OSA may result from the recurrent hypoxia-reoxygenation cycles [5]. In a recent meta-analysis, blood superoxide dismutase (SOD) concentrations were shown to be significantly lower in OSA patients than those in the controls, which suggests an impaired antioxidant defence in OSA [20]. Total oxidant status or malondialdehyde (MDA) level (a proxy for lipid peroxidation) were reported to be higher, whereas total antioxidant capacity (TAC) lower in untreated MDD patients as compared to those of the controls [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…Superoxide can easily react with NO itself, creating a highly toxic peroxynitrite (ONOO − ), a source of nitrosative stress leading to post-translational modifications of numerous proteins (nitration and S-nitrosylation) [ 5 ]. As far as the literature is concerned, it has been shown that the expression of superoxide dismutase (SOD), a key antioxidant enzyme, is significantly limited in subjects with OSA [ 6 ], whereas malondialdehyde (MDA), a commonly investigated marker of lipid peroxidation, is significantly increased in the course of OSA [ 7 ].…”
Section: Introductionmentioning
confidence: 99%